To eat or not to eat oats: factors associated with oats consumption using the I-Change model - S. Van Kol; H.C. van der Horst; H. de Vries (BMC, 2024)
Abstract A suboptimal diet is responsible for more deaths worldwide than any other risk. A dietary factor that needs more attention is whole-grain consumption because of its proven health, nutritional, and environmental benefits. Despite these benefits, the daily whole-grain and dietary fibre intake by Dutch residents is low and the reasons for this low consumption are unknown. This study analysed the facilitating and hindering factors associated with (non) oat consumption using the Integrated Change Model (ICM). It compared which factors distinguished oat consumers from moderate and low-oat consumers using a cross-sectional, quantitative study design. The questionnaire used in the quantitative study was based on the results a qualitative study that validated the findings identified in the literature and previous ICM studies. Data was collected using an online survey (Qualtrics). In both studies, the sample of participants included individuals age > 18, of both genders residents in the Netherlands without an allergy to oats, and who read or speak fluently Dutch or English. In total, 299 residents were included in the study. The results indicated that non-oat consumers were less health-conscious, had limited awareness of their dietary behaviours, possessed less knowledge, and were less aware of the severity and susceptibility to various health conditions, such as high cholesterol. They also received fewer prompts to consume oats, were less convinced of the rational and emotional benefits of oats, experienced less social support, reported more obstacles, and had lower self-efficacy regarding oat consumption. The Integrated Change Model (ICM) explained 55% of the variance in intention and 38% in behaviour. Consequently, efforts to promote oat consumption among Dutch adults should address these factors to enhance awareness, increase motivation, and facilitate actions to boost oat intake.